NGHIÊN CỨU KHU HỆ BƯỚM NGÀY (RHOPALOCERA: LEPIDOPTERA) TẠI KHU BẢO TỒN THIÊN NHIÊN MƯỜNG NHÉ, TỈNH ĐIỆN BIÊN, VIỆT NAM - Bùi, Xuân Phương (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
A STUDY ON BUTTERFLY FAUNA (RHOPALOCERA: LEPIDOPTERA) IN MUONG NHE NATURAL RESERVE, DIEN BIEN PROVINCE, NORTHERN VIETNAMThe study was carried out during period of June, 2014 in Muong Nhe Natural Reserve of Muong Nhe district, Dien Bien province, Northern Vietnam. There were 198 butterfly species belonging to 11 families and 105 genera of Lepidoptera: Ropalocera, inhabiting in Muong Nhe Natural Reserve. In comparison with the butterflies checklist of Hill and others (1997), our checklist provides 129 new records in this area. Among them 3 rare butterfly species listed in IUCN and Vietnam Red Data Book: Troides aeacus C. & R. Felder, Troides henena Linnaneus and Chilasa epicides Hewitson (Family: Papilionidae) were found.As a whole, Muong Nhe Natural Reserve appeared to be a suitable place for founding National Butterfly reserve in Northern Vietnam for faunistic and biological investigations and ecological tourism development.